??COPOLYMERIZATION OF METHYL METHACRYLATE (MMA) AND BUTYL ACRYLATE (BA) AND POLYBLENDS WITH CHLORINATED RUBBER (CR) (Biological Sciences - PJSIR, 2000)
Synthesis of MMA-Co-BA was accomplished at 60"C using benzoyl peroxide as initiator. It is observed that MMA and BAform copolymers in all monomeric ratios. Tensile properties and hardness were determined for the films prepared from theblends of chlorinated rubber and MMA-Co-BA. Tensile strength of the films increases as the amount of chlorinated rubber isincreased. The increase in tensile strength might be due to intermolecular and intramolecular rearrangements of copolymermolecules with chlorinated rubber and an increase in the crosslinking density of the system. The rearrangement of copolymermolecules with chlorinated rubber also enhanced the elongation at break. The addition of copolymer and plasticizer make thefilms more soft and flexible.